Long-Term Outcome of Juvenile Myoclonic Epilepsy - J Gordon Millichap (Pediatric Neurology Briefs Publishers, 2014)
Investigators at Epilepsy Centers in Berlin, Germany, performed a retrospective study of seizure outcome in 66 patients with juvenile myoclonic epilepsy (JME) after a mean follow-up time of 44.6 years (20-69 years); 59.1% of patients remained seizure-free for at least 5 years before the last contact.